Application of Lean Tools in different Industries: A review - et. al., Bhavani Sahua, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Many companies around the world were pressured to cut costs and become more mindful of consumer needs after the crisis hit at the turn of the twenty-first century. Industry has long seen Lean Manufacturing as a solution to these problems because it removes waste without requiring extra capital. In the current situation, Lean production principles and methods are commonly used by companies to optimise resource efficiency while minimising waste. Toyota has been recognised as one of the manufacturing techniques in improving efficiency, increasing customer loyalty, and thereby an organization's competitiveness, thanks to the Lean theory, which was developed by a Japanese scientist.